Characterization of the ESR response of alanine dosimeters to low-energy Cu-target X-tube photons. (November 2017) - Marrale, M.; Abbene, L.; d'Errico, F.; Gallo, S.; Longo, A.; Panzeca, S.; Tana, L.; Tranchina, L.; Principato, F.
Abstract: This article describes Electron Spin Resonance (ESR) response measurements of Kodak BioMax alanine films exposed to low-energy X-rays from a Cu-target tube operating at 20 kV. Commercial alanine detectors were used to ensure maximum reproducibility of the results, while the choice of a film was due the low penetration of the soft X-rays. X-ray energy spectra and fluences were determined with an innovative digital semiconductor detector system. These data were used to quantify the irradiation of the alanine films in terms of absorbed dose to water. The alanine films were found to present a stable response, highly linear with dose. To our knowledge, these data have not been previously reported and they may be extremely relevant, e.g., when mapping the high-gradient treatment fields used in microbeam radiation therapy (MRT) with synchrotron radiation. Highlights: ESR analysis of alanine films to low-energy photons produced by a Cu-target X-ray tube-system. ESR response to dose is linear and the signal is very stable in the first 40 days after irradiations. Possibility to use the alanine films for the dosimetry of beams produced by X-ray tube.